(untitled) (Research, Society and Development, 2022)
In addition to chronic diseases and empirical therapies against COVID-19, other factors are responsible for the high mortality rate associated with COVID-19. The objective of this study was to verify whether the exacerbated synthesis of inflammatory markers resulting from COVID-19 could compromise patients with coronavirus. The bibliographic research was performed in the Pubmed, LILACS, and SciELO databases between December 2020 and July 2021. For this study, the terms "COVID-19," "Biomarkers," "SARS-COV-2," and “Coronavirus 2019" are in advanced mode to gather the best evidence for the proposal of this manuscript. In the present construct, it is argued that COVID-19 increases the susceptibility of patients to a high stage of inflammation, increasing the virulence factors of the virus and its dissemination through the human body, where the synthesis of inflammatory factors plays a crucial role in the worsening of the cases. The virulence of the virus can be decreased by correcting the synthesis of these inflammatory markers, as it can prevent a less ineffective immune response and even increase the resistance of patients. Consequently, clinical trials in this direction should be carried out from the perspective of modulating responses at the molecular level, to find out how they work and how the underexpression of inflammatory cytokines may reduce the aggravation of patients with coronavirus.